Contribution to agrosilvopastoral zoning based on soil loss and climatological water balance (Research, Society and Development, 2021)
Environmental planning is an instrument for watershed management, enabling support for the decision-making process. The research aimed to create subsidies for decision making in the environmental planning of the land use of the Cachoeira Cinco Veados River Basin, RS. Based on the crossing of the potential soil loss (EUPS) and climatic water balance (BHC) variables, fragility classes were obtained for three rainfall scenarios with a pre-established soil loss limit. The most fragile classes are found in the largest classes of soil loss and in the minimal classes of climatological water balance. These results allow us to conclude the importance of continued environmental planning in the Basin, because even for minimal soil loss scenarios, 1.02% of the area (15.81 km2) is not allowed to be used according to the adopted criteria, that is, these areas show losses beyond the established limit.